Pengaruh Kemampuan Adaptasi dan Dukungan Pemerintah terhadap Ketahanan Bisnis yang Dimediasi Kemampuan Teknologi Informasi pada UMKM di Koperasi Konsumen Wanita Pengusaha Indonesia (KOWAPI) Srikandi Daerah Istimewa Yogyakarta - Astuti, Sri Endhri; Effendi, Irhas; Religia, Yoga (Universitas Batanghari, 2024)
This research aims to examine and analyze the influence of adaptability on business resilience, the influence of government support on business resilience, the influence of adaptability on information technology capabilities, the influence of government support on information technology capabilities, the influence of information technology capabilities on business resilience, the influence of adaptability on business resilience mediated by information technology capabilities and the influence of government support on business resilience mediated by information technology capabilities in MSMEs that are members of the Indonesian Women Entrepreneurs Cooperative (Kowapi) Srikandi DIY. The research method used was quantitative with a sample size of 80 respondents. The data collection technique was carried out using a questionnaire survey via Google Form and analyzed using SEM-PLS modeling analysis. The test results show that adaptability, government support and information technology capabilities have a positive effect on the resilience of MSME businesses in DIY. Information technology capability is a variable that explains the relationship between adaptability and government support on business resilience. This research focuses on confirming previous research regarding factors that influence MSME business resilience. It is hoped that future research will have broader and deeper objects, not only on MSME actors in the Kowapi